Balance of Payment Dynamic in Indonesia and the Structure of Economy - Telisa Falianty (Economics and Finance in Indonesia, 2017)
This paper will assess in aggregate and detail the trend of BOP and its component in Indonesia. Stationarity test will be employed to each component of Indonesian BOP to assess the persistency. This study will calculate the balance of payment constrained growth (BOPC) using Kalman Filter technique (state space model). The BOP, secondary income, and financial account are found to be stationer which means that the data are mean reverting. On the other hand, current account balance, trade balance, service balance, primary income, and capital account balance are unit root. This paper found the evidence of the importance of commodity price to Indonesian current account and export. Indonesian dependency on commodity-based export need to be restructured. Indonesia should also consider the side effect of FDI as a source of financing for current account deficit, without ignoring the positive effect of FDI and the volatility of portfolio investment. The persistency of primary income deficit should also become Indonesian future policy agenda.